The Equity Performance of Firms Emerging From Bankruptcy - Aggarwal, Reena; Altman, Edward I.; Eberhart, Allan C. (Journal of Finance, 1999)
This study assesses the stock return performance of 131 firms emerging from Chapter 11. Using differing estimates of expected returns, we consistently find evidence of large, positive excess returns in 200 days of returns following emergence. We also examine the reaction of our sample firms' equity returns to their earnings announcements after emergence from Chapter 11. The positive and significant reactions suggest that our results are driven by the market's expectational errors, not mismeasurement of risk. The results provide an interesting contrast, but not a contradiction, to previous work that has documented poor operating performance for firms emerging from Chapter 11.